2011
DOI: 10.2298/jmmb101012002s
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the formation mechanism of the TiFe alloy by the molten-salt electrolytic titanium concentrate

Abstract: The ferrotitanium alloy was prepared in the molten CaCl2 system, in which resolidified ilmenite and the graphite crucible were used as cathode and anode. In this study, the electrolytic voltage was fixed at 3.1V, and three different temperatures were applied: 850oC, 875oC and 900ºC. Finally, the product was examined by SEM and XRD to determine the phase transformation after the electrolysis. The results show that the ilmenite was firstly reduced to Fe, and finally the TiFe alloy was formed. The intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…In Fig. 5c, additional phases (iron titanium and iron titanium oxide phases) are composed and can be seen in 2θ = (42) and (32, 36) 28,29 . The results indicated that iron and aluminum entered into the crystal lattice of titanium dioxide.…”
Section: Xrdmentioning
confidence: 98%
“…In Fig. 5c, additional phases (iron titanium and iron titanium oxide phases) are composed and can be seen in 2θ = (42) and (32, 36) 28,29 . The results indicated that iron and aluminum entered into the crystal lattice of titanium dioxide.…”
Section: Xrdmentioning
confidence: 98%
“…It has been a hotspot issue to directly prepare titanium or titanium alloy from titanium oxides by the electrochemical reduction. Molten salt electrolytic methods, as a short process and direct preparation of titanium alloys, is becoming an issue with an increased concern, while it has not been used in a real production due to the limits of electrode materials and current efficiency [3][4][5][6][7][8]. Thermite method (also called thermite reduction), using aluminum as a reductant and high-grade ilmenite as raw materials, is another short process of directly producing high titanium 2 of 10 ferroalloy.…”
Section: Introductionmentioning
confidence: 99%
“…This process would inevitably emit large quantities of CO 2 greenhouse gas. It is well known that high-temperature direct electrolysis is a basic method to produce some metals and alloys [1][2][3][4][5]. To solve thoroughly the problem of CO 2 emissions in ironmaking process, several researchers have explored direct electrolysis to prepare iron in recent years, such as the molten salt electrolysis method of G. Haarberg [6] and G.M.…”
Section: Introductionmentioning
confidence: 99%